Implementation of the Protection Policy for Children with Disabilities in the Rumah Anak Prestasi Surabaya City - Pramesti, Tarisa Indah; Wibawani, Sri (Borong Newinera Publisher, 2024)
Implementation of the policy for protecting children with disabilities in Rumah Anak Prestasi (RAP) by referring to Surabaya City Regional Regulation Number 3 of 2023 concerning Amendments to Regional Regulation Number 6 of 2011 concerning Implementation of Child Protection. The number of children with disabilities in Surabaya City in 2023 is 2,562 children, this is not comparable to the number of registrants in the 2023 RAP, a total of 599 children. The research method used is descriptive qualitative. Data collection was carried out by observation, interviews and documentation. There were 4 informants, the Head of the Rehabilitation Division at the Surabaya City Social Service, the Head of the State Children's Village UPTD, RAP administrative staff, and the parents of participants at the Achievement Children's Home. Data analysis (1) data condensation, (2) data display, and (3) drawing conclusions/verification. The results of the research on the implementation of the policy for protecting children with disabilities at the RAP were said to be successful with various training and services provided to participants at the RAP in Semolowaru and Sonokwijenan. Conclusion: The implementation of the policy for protecting children with disabilities in the City of Surabaya (case study of the Achievement Children's Home) was successful, seen from the various training and services provided to participants of the RAP in Semolowaru and Sonokwijenan. However, the organizational capability, information and support factors need to be improved.